Molecular Detection and Antibiogram of Bacterial Isolates from Canine Pyoderma Cases - Milandahalli, Chaithanya; Thimmaiah, Ramesh Poojary; Munishamy, Chandrashekar Kodavenakapalli; Shekharaiah, Lathamani Venkatapura; Ramakrishna, Anjan Kumar Keeramande; Jayanna, Renukaradhya Gudepalya (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Canine pyoderma is one of the most common causes of dermatitis with worldwide occurrence in small animal practice. This study was  carried out to identify bacterial isolates by simplex, multiplex PCR and to know its antibiotic susceptibility profile from canine pyoderma  cases. Staphylococcus intermedius (n=17, 53%) was the major species identified followed by Staphylococcus schleiferi (n=10, 32%),  Staphylococcus aureus (n=6, 15%), Pseudomonas aeruginosa (n=5, 12.5%) and Escherichia coli (n=3, 7.5%) by PCR. Antibiogram profile  of Staphylococcus isolates showed sensitive to enrofloxacin (84.37%), ceftriaxone (81.25%), ceftriaxone/tazobactam (62.5%), whereas  P. aueroginosa was sensitive to meropenem (100%), ciprofloxacin (100%), ceftriaxone/tazobactam (80%) and E. coli was sensitive to  meropenem (100%), ceftriaxone/tazobactam (100%), ampicillin/sulbactam (100%). All isolates of this study were resistant to pencillin  G, clindamycin (P. aueroginosa and E. coli), co-trimoxazole (Staphyloccous spp. & P. aueroginosa) and streptomycin (E. coli) indicating  frequent and indiscriminate use of these antimicrobials in pyoderma treatment.
Keywords: Antibiotic susceptibility; Canine pyoderma; Meropenem,; PCR; Penicillin G; Staphylococcus.